Gaseous ozone-enrichment for the preservation of fresh produce - Tzortzakis, Nikos G. (My University, 2015)
Ozone is considered the most economically important air pollutant worldwide. Experimental studies reveal contrasting effects of ozone on foliar pathogens with several successful applications in postharvest level. Oranges, grapes and tomatoes were infected with green mould (Penicillium digitatum) and grey mould (Botrytis cinerea), then fruit incubated in 'clean air' or an ozone-enriched atmosphere (concentrations ranging from 0.05 to 1.0 ppm). In vivo and in vitro experimentation revealed lesion development and spore production to be markedly reduced in fruit maintained in an ozone-enriched atmosphere. Higher concentrations/duration of exposure resulted in greater impacts on lesion development/spore production, with considerable benefits resulting from exposure to low levels of ozone (i.e., below the 0.2 ppm threshold set for the protection of human health). In vitro studies performed on fungi raised on potato dextrose agar (PDA) for 6-8 days at 13°C and 95% relative humidity (RH) revealed no direct effects of ozone on fungal development, implying that suppression of pathogen development was due in a large part to the impacts of ozone on fruit-pathogen interactions.
Keywords: Modified atmosphere storage; Ozone-enrichment; Postharvest fungal pathogens; Spoilage